From Shame to Acceptance: Identity Reconstruction in Clients with Borderline Personality Disorder - Petrov, Georgi; Dimitrov, Ivan (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aims to explore the process of identity reconstruction from shame to self-acceptance in individuals diagnosed with Borderline Personality Disorder (BPD).Methods and Materials: A qualitative research design was employed, involving semi-structured interviews with 24 participants diagnosed with BPD, all residing in Bulgaria. Data collection focused on exploring the participants' lived experiences of shame, identity disturbance, and their therapeutic journey toward self-acceptance. Thematic analysis was used to analyze the data, with NVivo software supporting the coding process. Theoretical saturation was reached, ensuring comprehensive representation of the themes.Findings: The analysis revealed four main themes: Internalized Shame, Identity Confusion, Therapeutic Transformation, and Pathways to Acceptance. Participants described pervasive feelings of shame rooted in childhood trauma, leading to identity fragmentation and relational instability. The therapeutic alliance, emotional validation, and narrative restructuring emerged as key processes in identity reconstruction. Participants reported a gradual shift from self-criticism to self-compassion, facilitated by therapy, which helped in the integration of their past and present selves. Despite setbacks, participants experienced significant improvements in self-worth and emotional regulation.Conclusion: This study highlights the crucial role of shame in the development of identity disturbance in BPD. The therapeutic process, characterized by a strong therapeutic alliance and self-compassion, is integral to the reconstruction of identity from shame to acceptance. Future research should focus on comparative studies of therapeutic approaches and explore the long-term impact of therapy on identity consolidation in BPD.